Developmental programming: Prenatal bisphenol A treatment disrupts mediators of placental function in sheep. (March 2020) - Song, Wenhui; Puttabyatappa, Muraly; Zeng, Lixia; Vazquez, Delia; Pennathur, Subramaniam; Padmanabhan, Vasantha
Abstract: Gestational Bisphenol A (BPA) exposure is associated with low birth weight. We hypothesized that the low birth weight is the consequence of reduced placental efficiency and a function of BPA-induced inflammatory, oxidative, lipotoxic, angiogenic, steroidal and fibrotic changes involving epigenetic alterations. Placentomes were collected during early (day 65) and mid (day 90) gestation (term ∼147 days) from control and BPA (gestational day 30–90)-treated pregnant sheep. BPA treatment: reduced placental efficiency and fetal weight; increased interleukin 8, lipid peroxidation marker, antioxidants, aromatase, 17 alpha-hydroxylase, estrogen receptor 2, insulin like growth factor (IGF) 2 receptor and IGF binding proteins (IGFBP), and histone deacetylase 1 and 2; reduced tumor necrosis factor alpha and IGF1 receptor at early gestation (Day 65). Gestational BPA-induced mid-gestational changes include: reduced angiogenic factor hypoxia inducible factor 1 alpha; increased IL1beta, oxidative stress markers, triglyceride, 17alpha hydroxylase, IGFBP 1, DNA methyltransferase 3 A and histone deacetylase 1. These findings indicate that gestational BPA, either acting directly or by altering steroidal input, produces early/mid-gestational-specific epigenetic changes culminating in placental disruptions at several levels, in keeping with time-specific/time-lagged pregnancy-associated changes in placental efficiency and fetal weight. The reduced early-gestational placental efficiency may be a function of increased inflammation/oxidative stress and reduced IGF bioavailability with the mid-gestational restoration of placental efficiency likely driven by improved IGF bioavailability and the time-lagged response to antioxidant increase. This compensation, the result of time-lagged response to increases in negative mediators of placental function must have failed with pregnancy advancement to explain the low birthweight outcome. Highlights: Exposure to BPA compromises early pregnancy placental efficiency. Gestational BPA exposure disrupts several mediators of placental function. BPA-induced effects on placental mediators differ between early and mid-gestation. Gestational BPA exposure induces pregnancy stage-specific epigenetic alterations. Effects of gestational BPA may involve changes in placental steroid milieu.